Bezpieczeństwo kulturowe przesłanką konstruowania tożsamości młodego pokolenia na styku kultur. Ku jakiej tożsamości? - Szerląg, Alicja (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2018)
The identity of the individual is constructed in cultural references. This process becomes even more complex, when occurring in the multicultural area. As a result, the specificity of identities is influenced by diverse identifications taking place with reference to objects of own and different cultures. A sense of cultural safety plays an important role in this process, not only guaranteeing the certainty of existence and development of the national identity of individuals and cultural community, but it also allows – to a different degree – to open one self to different cultures.
Keywords: cultural identity; cultural safety; cultural self-identification; creators of cultural identity; multi-range identity; multidimensional identity